Cultivating meaningful experiences: the impact of psychological climate on voluntary pro-environmental behavior and proactive customer service performance - Yang, Boya; Ho, Jo Ann; Ng, Siew Imm; Jun Hwa (Jacky), Cheah (2024)
This study investigates the impact of psychological climate (PC) on hotel employees' voluntary pro-environmental behavior (VPEB) and proactive customer service performance (PCSP). Drawing on the broaden-and-build theory, we explore how experienced meaningfulness (EM) mediates the relationship between PC and discretionary behaviors, and how interdependent self-construal (InterSC) moderates these effects. Data from 603 employees and 201 supervisors in Macau’s upscale hotels reveal that positive PC enhances EM, leading to increased VPEB and PCSP. The findings offer insights into fostering sustainable practices and exceptional service in the hospitality industry by promoting a supportive work environment and considering individual differences in self-construal.